Mengaburkan Realitas Melalui Bahasa: Kode Sosiokultural Jepang dalam Dialog Horor pada Serial Animasi Yami Shibai: Blurring Reality Through Language: Japanese Sociocultural Codes in Yami Shibai's Horror Dialogues - Abdul Gapur; Taulia; Muhammad Yusuf; Alvy Mawaddah; Laraiba Nasution (Undiksha Press, 2026)
This article analyzes the linguistic strategies used to blur the boundary between reality and hallucination in the Japanese horror anime series Yami Shibai Season 10, while reflecting on the underlying Japanese sociocultural codes. The study employs a descriptive qualitative approach and an interpretive case study method, examining transcripts from the first five episodes. The analysis utilizes Norman Fairclough’s critical discourse analysis framework, integrated with the Japanese cultural concepts of uchi/soto and tatemae/honne. The findings identify three main linguistic strategies: (1) referential incongruity and linguistic personification; (2) ambiguous spatial–temporal deixis; and (3) unnatural conversational registers. The analysis demonstrates that these strategies interact with and are reinforced by the Japanese cultural framework. The transgression of uchi/soto boundaries and the tension between tatemae and honne transform linguistic ambiguity into a distinct horror aesthetic. In conclusion, language in Yami Shibai serves as a cultural instrument that not only generates fear but also reflects the structural anxieties of contemporary Japanese society.